Regulation of HSP70 synthesis by messenger RNA degradation. - Petersen, R.B.; Lindquist, S. (Cell Regulation, 1989)
When Drosophila cells are heat shocked, hsp70 messenger RNA (mRNA) is stable and is translated at high efficiencies. During recovery from heat shock, hsp70 synthesis is repressed and its messenger RNA (mRNA) is degraded in a highly regulated fashion. Dramatic differences in the timing of repression and degradation are observed after heat treatments of different severities. The 3' untranslated region (UTR) of the hsp70 mRNA was sufficient to transfer this regulated degradation to heterologous mRNAs. Altering the translational efficiency of the message or changing its natural translation-termination site did not alter its pattern of regulation, although in some cases it changed the absolute rate of degradation. We have previously shown that hsp70 mRNA is very unstable when it is expressed at normal growth temperatures (from a metallothionein promoter). We report here that the 3' untranslated region of the hsp70 mRNA is responsible for this instability as well. We postulate that a mechanism for degrading hsp70 mRNA pre-exists in Drosophila cells, that it is inactivated by heat shock and that it is the reactivation of this mechanism that is responsible for hsp70 repression during recovery. This degradation system may be the same as that used by other unstable mRNAs.